Water Quality Assessment of Bichlari Nala Flowing through Banihal and Ramban (Jammu & Kashmir) - Tikoo, Veerji; Verma, R. K.; Fotedar, Amita; Fotedar, B. K. (Indian Forester, 2008)
Chemical analysis of water flowing in Bichlari Nala was carried out for Ca, Mg, K, Na, Fe, Mn, Cu, Ni, Zn and Pb. The analysis revealed all cations are below the permissible limits except Fe, Mn and Ni, which are above permissible limits and hence toxic for human consumption. As far as agricultural use of this water is concerned, no element is in higher concentration and hence is non-hazardous for crops. Bicarbonates, sulphates and nitrates, total hardness values are all within safer levels. Turbidity values are higher because of higher rate of erosion in the catchment areas. pH of all the samples is within the permissible limits. SAR (Sodium Absorption Ratio), SSP (Sodium Soluble Percentage) and RSC (Residual Sodium Carbonate) values are too low to cause any type of soil hazard. Proper hygienic filtration and disinfection with chlorine/bromine is recommended to render the waters fit for human consumption. Besides disinfection, vetiver grass needs to be grown abundantly in and around Banihal town and steep hills existing on both the banks of Bichlari stream. This will check fast erosion by binding the soil together and also will screen many of the cations including Fe, Ni and Mn to enter into the solution of the waters. Last, but not the least, is to create mass awareness among the residents of all the villages existing in the areas between Banihal and Ramban towns for maintaining a good sanitation throughout. Deforestation in the catchment areas of Bichlari Nala should be stopped forthwith with strong hands to protect mass wastage, landslides and contamination in waters.